Childhood Maltreatment, Trauma, and Abuse and Adolescent Delinquency, United States, 1994-2008 - Wilkinson, Andra ([Verlag nicht ermittelbar], 2018)
These data are part of NACJD's Fast Track Release and are distributed as they were received from the data depositor. The files have been zipped by NACJD for release, but not checked or processed except for the removal of direct identifiers. Users should refer to the accompanying readme file for a brief description of the files available with this collection and consult the investigator(s) if further information is needed. This collection features secondary analyses of restricted-use data from the National Longitudinal Study of Adolescent to Adult Health (Add Health), a nationally representative longitudinal study of a sample of U.S. adolescents who were in grades 7-12 in the 1994-95 school year, who were interviewed at three key developmental junctures from adolescence to young adulthood. Self-reported data were used for both maltreatment (measured at the latter two time points) and delinquent or criminal behaviors (measured at all three time points). Linear mixed-effects analyses were used to model growth curves of the frequency of violent and non-violent offending, from ages 13 to 30. Next, maltreatment frequency was tested as a predictor, and then potential protective factors (at peer, family, school, and neighborhood levels) were tested as moderators. Sex, race/ethnicity, and sexual orientation were also tested as moderators of delinquent or criminal offense frequency, and as moderators of protective effects. The study collection includes 1 Stata (.do) syntax file (AddHealthOJJDPAnalysis_StataSyntax.do) that was used by the researcher in secondary analyses of restricted-use data. The restricted archival data from the Add Health survey series are not included as part of this release.